2014
DOI: 10.1136/neurintsurg-2014-011366
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of acute intracranial vertebral artery dissection: long-term follow-up results of internal trapping and reconstructive treatment using coils and stents

Abstract: This study suggests that internal trapping is a stable and effective treatment for acute VAD. Reconstructive treatment using stent and coils could also be a feasible alternative modality for hemorrhagic type VAD. However, serial DSA follow-up is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…9 For treatment of acutely ruptured type 1 aneurysms of the posterior circulation, stent-assisted coiling has become the treatment of choice. 10 There is sparse literature on the use of FDs in this clinical setting. In our study, FDs alone and FDs in combination with coils resulted in acceptable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…9 For treatment of acutely ruptured type 1 aneurysms of the posterior circulation, stent-assisted coiling has become the treatment of choice. 10 There is sparse literature on the use of FDs in this clinical setting. In our study, FDs alone and FDs in combination with coils resulted in acceptable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As lower cranial nerve palsy may induced after direct surgery, endovascular treatment, which facilitates prompt, minimally invasive intervention, is primarily selected as a first-line procedure for ruptured VADs. Recent studies reported favorable results of endovascular treatment with stents, including flow-diverting stents [3][4][5][6] which has been emphasized as a treatment method to prevent rebleeding while maintaining parent vessel blood flow. However, the treatment with stents for ruptured VADs has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…Internal trapping is still a first choice of endovascular procedures for ruptured VAD. 5,6) However, it was also indicated that internal trapping frequently causes medullary infarctions related to occlusions of perforating arteries arising from vertebral arteries (VAs). 7,8) Medullary infarctions may induce dysphagia or aspiration pneumonia, and is regarded as one of the most important prognostic factors.…”
Section: Introductionmentioning
confidence: 99%
“…When vertebral artery dissection aneurysms occur the recurrent ischemic symptoms, progressive enlargement, mass effect, or subarachnoid hemorrhage (SAH), the following treatments, such as surgery or endovascular treatment, may be considered. Because surgery involves high risks for treatment-related morbidity and mortality [1], deconstructive [2][3][4][5] (proximal occlusion or internal trapping) and reconstructive techniques [4][5][6] are increasingly emerging as an alternative to surgery to treat these lesions in deep locations. For deconstructive techniques with a higher rate of perioperative morbidity [7], stent-related reconstructive treatment is increasingly focused for the maintaining integrity of the posterior inferior cerebellar artery (PICA) and parent artery.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reasons include the different etiology and more complicated anatomic configurations [10], such as intramural hematomas, pearl-and-string configurations, intimal flap configurations, PICA-involving, and so on. In contrast, multiple-stent-assisted coiling for sis-VADA is increasingly focused and achieves the encouraging results [5,6]. The overlapping multiple stents are better than single stent in decreasing intra-aneurismal wall shear stresses [11][12][13], which prevent coil compaction, aneurismal rupture and growth.…”
Section: Introductionmentioning
confidence: 99%